O-182 Higher risk of preeclampsia and pregnancy-induced hypertension with artificial cycle for Frozen-thawed Embryo Transfer compared to ovulatory cycle or fresh transfer following In Vitro Fertilization. (6th August 2021) - Epelboin, S; Labrosse, J; Fauque, P; Levy, R; Mouzon, J. De; Boyer, M; Vienne, C. De; Bergere, M; Valentin, M; Devaux, A; Hester, L; Sermondade, N; et al.
Abstract: Study question: Is there an increased risk of preeclampsia after Frozen-thawed Embryo Transfer(FET) compared to In Vitro Fertilization-fresh transfer(IVF-fresh-ET) according to endometrial type of preparation for FET? Summary answer: The frequency of preeclampsia and hypertension were significantly higher in the group of artificial cycle (AC-FET) compared to ovulatory cycle (OC-FET) and fresh-ET (P < 0.0001). What is known already: Risks of maternal morbidity are known to be reduced in pregnancies resulting from FET compared to fresh-ET except for the risk of preeclampsia, that was reported to be significantly higher in pregnancies resulting from FET compared to fresh-ET or spontaneous conception. Most recent studies demonstrate an equal live birth rate with either OC-FET or AC-FET preparation. Few studies compared the maternal vascular morbidities with the two hormonal environments that preside over the early stages of embryonic development: OC (major role of the corpus luteum) and AC (prolonged hormone replacement with high doses of estrogen and progesterone). Study design, size, duration: We conducted a 2013-2018 French nationwide cohort study comparing maternal vascular morbidities in 3 groups of single pregnancies> 22 weeks of gestation (WG): FET with AC or OC preparation, and IVF (conventional or ICSI)-fresh-ET.Data were extracted from the French National Health System database (>99% of national deliveries) in which all hospitalizations are registered, containing information on patient characteristics, diagnoses and treatments. Records were merged anonymously. Access to the database was legally approved. Participants/materials, setting, methods: 68 025 deliveries were included: fresh-ET(n = 48 152), OC-FET(n = 9 500), AC-FET(n = 10 373). In OC-FET, a luteal phase support with progesterone was administered for maximum 6 WG if pregnancy. In AC-FET, progesterone was co-administered with estrogen until 12 WG. Embryos were transferred at cleavage or blastocyst stage. Vascular disorders were recorded if hospitalization for preeclampsia/eclampsia or hypertension (history of hypertension excluded). Maternal characteristics were included in multivariate analysis. Adjusted odds ratios(aOR) and 95% confidence intervals(CI) were estimated. Main results and the role of chance: Maternal characteristics: In multivariate analysis, patients in the FET groups were older (33.4 years (std=4.3) vs. 33.2 years (std=4.4) for fresh-ET, respectively, P < 0.0001), less often primiparous (aOR=0.68[0.66-0.71], P < 0.0001) or smokers (aOR=0.84[0.75-0.95]) or with premature ovarian insufficiency (POI) (aOR=0.68 [0.58-0.79]), more frequently with polycystic ovaries (PCOS) (aOR=1.25[1.12-1.39]) and comparable for obesity or diabetes. In FET groups, 52.2% were AC-FET. There was no difference for maternal age, parity, obesity, smoking, history of diabetes between AC and OC-FET. Endometriosis (aOR=1.26[1.16-1.38]), PCOS (aOR=1.79[1.50-2.15]) and POI (aOR=2.0[1.48-2.72]) were more frequent in AC-FET. Risks of vascular disorders: The rate of preeclampsia (5.3% vs. 2.3% vs. 2.4%, respectively, P < 0.0001) and hypertension (4.7% vs. 3.4% vs. 3.3%, respectively, P = 0.0002) was significantly higher in AC-FET versus OC-FET and fresh-ET. In multivariate analysis, the risk of preeclampsia increased with age, primiparity, obesity, diabetes and POI. The risk was higher in AC-FET versus OC-FET (aOR=2.42 [2.06-2.85]) and fresh-ET (aOR=2.43[2.2-2.7]), P < 0.00001. No difference was found between OC-FET and fresh-ET (P = 0.91). The risk of pregnancy-induced hypertension increased with age >40, primiparity, smoking, obesity and diabetes and was higher in AC-FET versus OC-FET (aOR=1.50[1.29-1.74], P < 0.0001) and fresh-ET (aOR=1.50[1.35-1.67], P < 0.0001) and not different between OC-FET and fresh-ET (P = 0.86). Limitations, reasons for caution: While the strength of this study relies in the number and exhaustiveness of subjects analysed, its limitations are its retrospective and register-based nature that did not enable to refine the risk according to details of techniques and treatments in each group. Wider implications of the findings: This large nationwide cohort study highlights 2 important information for physicians : i) the possible deleterious role of high supra-physiological and prolonged doses of estrogen-progesterone supplementation on vascular pathologies ii) the protective role of the corpus luteum present in stimulated or spontaneous OC for their prevention. Trial registration number: Not applicable